If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7f + 5 = 5f + 17 Reorder the terms: 5 + 7f = 5f + 17 Reorder the terms: 5 + 7f = 17 + 5f Solving 5 + 7f = 17 + 5f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-5f' to each side of the equation. 5 + 7f + -5f = 17 + 5f + -5f Combine like terms: 7f + -5f = 2f 5 + 2f = 17 + 5f + -5f Combine like terms: 5f + -5f = 0 5 + 2f = 17 + 0 5 + 2f = 17 Add '-5' to each side of the equation. 5 + -5 + 2f = 17 + -5 Combine like terms: 5 + -5 = 0 0 + 2f = 17 + -5 2f = 17 + -5 Combine like terms: 17 + -5 = 12 2f = 12 Divide each side by '2'. f = 6 Simplifying f = 6
| 41x=14 | | I=(89)(.075)(.5) | | 4x-6x+2x-8x= | | 3x+(2x+10)=5 | | 18s=10 | | (8x+22)=(5x+15) | | 0.4*x=X-100 | | 18+6.50(x-3)= | | 725.4656=4*3.14*r^2 | | 4392.1064=4*3.14*r^2 | | y=17sin(8t) | | a^2+7ab-18n^2=0 | | 8x-37=4x+27 | | -5k-4(k-3)=-6k+3 | | 5(x+2)-3=2x+3(1+x) | | 40*x=X-100 | | 6m^2+2m-17=0 | | (2x+6)+(x+9)=90 | | 2x-3y(x-1)=-1 | | -k+35=-7(-5-8k) | | 107+2x-5=180 | | 2(2+3y)+3y=15 | | x+2x-5=107 | | 9x^2-70+49=0 | | 2x+-3y(6x-11)=-7 | | (6x^2)-30x=0 | | (6x^2)-30y=0 | | (6x+48)=(12x+24) | | 26.2=9t | | 3b-3-4b=2 | | 10=1+r+5 | | y=4+0.01x |